E-Teach : Mobile Application Teaching Administrative System Using Near Field CommunicationN (NFC) - F Ferry; Dedy Prasetya Kristiadi; S Sutrisno (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Teaching administration is a teacher's needs that are recorded or recorded into files stored by the school curriculum section. Teaching administration is in the form of lesson plans per semester made by the teacher to be applied based on the planned subject matter. Archiving of learning outcomes data and teaching materials is often ignored so that teachers do not provide subject matter according to the study plan and evaluation of learning outcomes is not satisfactory. In addition, the teacher administration file is a need for school accreditation which is a benchmark for the education office's assessment, which is a serious concern for schools in making reports in their work units. To reduce administrative errors, loss of data and the effectiveness of teaching services and assist teachers in managing lesson plans and evaluating learning outcomes, a tool that is able to provide solutions is needed. Near Field Communication, abbreviated as NFC, is a development tool for Bluetooth and RFID. NFC allows the phone to store important data securely and sent to other phones equipped with NFC or read by an NFC reader. In addition, this NFC allows mobile phones to be developed for the administration of school payments as well as giving class schedules to students. In this study, a teaching administration system based on Near Field Communication (NFC) has been developed using the Raspberry Pi as a microcontroller as well as a computer capable of applying web-based programs. Electronic teaching administration with NFC is expected to replace conventional teaching administration. The advantages of NFC-based E-Teach are that it takes a short time to use, does not depend on internet access and is easy in delivering teacher administration to those in need. Study plan data processing and evaluation of student learning outcomes are faster, more accurate and integrated with the management of education providers.